KEBIJAKAN PENANGGULANGAN INFLASI DI INDONESIA - NOPIRIN NOPIRIN (Journal of Indonesian Economy and Business (JIEB), 1997)
This paper begins with a theoretical discussion on the causes of inflation.Inflation can occur as a result of rising aggregate demand (demands pull inflation) and upward shifting aggregate (costs push inflation). Aggregate demand consist of household expenses, government expenses andnet export, whereby those components are transformed as a result of monetary and finance policies, and balance of payment Inflation occurs when rising aggregate demands are not followed by rigidities in aggregate supplies. Budget deficits that are paid by printing of currencies without equal response from production will increase pressure for inflation. Deficit of balance of payment will lead to depreciation of domestic currency, which in the case of high volume of import industry will lead to rising pressure for inflation. Inflation pressure can also be caused by the increasing in aggregate supplies, as a result of rising production costs.Indonesia's experience in overcoming inflation began with the phenomenon of uncontrolled inflation in the Old Order, where national budget deficit was financed by loans from Bank Indonesia. During the New Order, high inflation is overcome by the initiation of balanced budget programs and by encouraging production. The government stimulates foreign and domestic investment, as shown by the formulation ofUUPMA and UUPMDS in 1968. Besides monetary policies to counter inflation, the government also revives aggregate supplies by deregulating the production sector.